K-Means Analysis in Sharia Banking Intellectual Capital - Ana, Selvia Roos; Indrianasari, Neny Tri; Liyundira, Fetri Setyo (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This research aims to assess the need to manage and increase Intellectual Capital efficiently in the context of Sharia BPR. Design/methodology/approach: Using secondary data to categorize BPR Sharia banks in East Java Province based on the level of the intellectual model using the K-Means method. Findings: The k-means method with a two-group configuration is the best approach for clustering. The second group has a high amount of Intellectual Capital, while the first group has a low amount of Intellectual Capital. Managing Intellectual Capital to increase added value for the company is a challenge for 10 Sharia BPRs in East Java Province Research limitations/implications: Data collection is limited to 2022 and focuses on 10 Sharia BPRs in East Java Province, which can provide a limited picture of the dynamics of change over a longer period or at the national level. Practical implications: The results of clustering BPR Syariah using the K-Menas method provide a basis for practitioners to group BPR Syariah based on the level of intellectual capital so as to help banks identify intellectual capital management and use this information to design more targeted strategies. Originality/value: This research involves the application of the K-Means technique in classifying intellectual capital in the context of sharia banking so as to provide more accurate and structured insight into the potential and utilization of intellectual capital in the context of sharia finance.